Handbook Development to Create Expressive Drawings for Grade 2 Students in an Islamic Primary School Ambarawa Semarang - Widyaningrum, Deni Setiawan, Kurnia (Elementary School Teacher, 2018)
Based on the observation data the learning result of grade IIA showed average score in 70,4. 14 students (46%) are still under criteria and 16 students (54%) have reached criteria, that is 75. To solve the problem the researcher develops guide book to create an expressive picture. The result of this research in composing a guide book was design using CorelDraw X5 and Ms. Word 2010 on the content of the book, with A4 size and portrait shaped. The result of the media properness asessmen the guide book to create an expressive picture get score 85% and it is stated very proper and the content asessmen get score 81, 25% and stated very proper. The effectiveness of the use guide book has pretest average score is 56,2.While post test average score is 86. The result of N gain is obtained at 0,67 including in middle the value of category. Testing with significant level 0,05 . ttable is 2,08 ang tcount is 69,28, so H0 is rejected. The conclussion is the used of guide book to create an expressive picture is proper and effective